Sugar Alcohol: A Comparison of Xylitol and Sorbitol in Food Application - Asasta, Abhirama Radya; Armando, Dechen Wangmo; Tissadharma, Janice Clarisa; Theo, Kimberly Alecia; Nobelta, Natasya (International Journal Labs, 2024)
Sugar is commonly used on a daily basis but, consuming excessive sugar can lead to various health issues such as diabetes, cardiovascular, and respiratory illnesses. As a result, the food industry has been manufacturing artificial sweeteners in order to reduce the risk of disease development. This research aims to compare the roles of xylitol and sorbitol based on their chemical value, as well as the benefits and drawbacks of their use in food applications. Sugar alcohols are mostly employed as thickeners and sweeteners and are additionally referred to as bulk sweeteners. Xylitol is typically found in fruits, vegetables, and hardwood trees. Furthermore, when compared to sucrose, xylitol includes similar tastes and sweeteners, though insulin is not required during metabolism. Additionally, it is used in healthcare products such as toothpaste and mouthwash due to its ability to prevent tooth decay. Similarly, sorbitol can be found in fruits and vegetables and is frequently employed as a sweetener, texture enhancer, and moisture maintainer. Nevertheless, xylitol and sorbitol may have their own set of advantages and disadvantages. It has been found that xylitol has a wide range of potential health benefits, including lower blood glucose and insulin response, and less sweetness intensity than sucrose. However, a drawback of ingesting xylitol is that it provides low-GI energy, making it unsuitable for people with low glucose levels, and it has a lower laxation threshold. Sorbitol also provides health benefits as it supplies calories and has a low glycemic index.